USERS’ INTENTION TO USE AN E WALLET INTEGRATED WITH E-HEALTH - Kelvin Yong, Ming Lee; Pick Soon, Ling; Mohamad, Jais (Academic Inspired Network, 2022)
: This study proposed the integration of E-health function into the E-wallet. With the E-health function, users able to get the workout suggestion for the food purchased or consumed by them. This study extends the technology acceptance model (TAM) by including the social media addiction as the potential factor. This study also successfully collected 240 responses. The findings confirm that perceived usefulness, perceived ease of use and social media addiction are positively related to the attitude toward the integration of E-health function into E-wallet. This attitude is also positively related with the user’s intention in using this proposed new function. The outcome of this study may serve as a guideline to enhance the existing Ewallet to attract the potential users. This study also recommends the E-wallet provider to deliver information through the social media. By using this way, E-wallet provider may also attract the potential users who are addicted to social media.